Evidence and Open Questions for the Use of Video-Feedback Interventions With Parents of Children With Neurodevelopmental Disabilities - Provenzi, Livio (Front Psychol, 2020)
The Video-Feedback Intervention (VFI) is a technique aimed at promoting positive parenting that has been found to be supportive of child development and parent–child interaction in different at-risk and clinical populations. The application of VFI with parents of children with neurodevelopmental disabilities (ND; e.g., cerebral palsy, sensory and/or psychomotor delay, and genetic syndromes) is growing. Nonetheless, no systematic review is currently available documenting whether this type of intervention improves children’s developmental outcomes (e.g., behavioral stability and cognitive abilities), parental caregiving skills (e.g., responsive parenting), and parental emotional well-being (e.g., depressive symptomatology). In the present mini-review, 212 VFI records were retrieved from three databases (i.e., PubMed, Scopus, and Web of Science), and 10 papers were finally included. Abstracted information included age, diagnosis, methodological aspects (timing, setting, and themes), and child/parent outcomes. Significant improvements from pre- to post-VFI were observed in all studies. Specifically, the VFIs were significantly associated with better children developmental outcomes and parental caregiving skills. Inconsistent findings emerged for the VFI effects on parental emotional well-being. Overall, the current mini-review supports the potential effectiveness of parent-focused VFI interventions for parents of children with ND, despite the presence of open questions that need to be addressed in future clinical trials.